Task-specific ionic liquids synthesized in silica by the sol-gel method. Characterization and application to model reactions: Esterification and transesterification - María B. Martini; Valeria Palermo; Gustavo P. Romanelli; Claudia G. Adam (Next Materials)
Ionic liquids (ILs) have unique properties that make them attractive to be used as catalysts in numerous reactions, although their separation and recovery from the reaction media use to be challenging. Thus, it is possible to add value to ILs from a technological point of view, by immobilizing them in solid materials and maintaining their specific catalytic properties. This work reports the catalytic behavior of a new class of 'task-specific ionic liquids' (TSILs) that are encapsulated inside the pores of silica particles synthesized through the sol-gel method. The 1-(4-sulfonic acid)-butyl-3-methylimidazolium ([bsmim]) and 1-(4-sulfonic acid)-butyl-imidazolium ([bsHim]) with bisulphate as the counterion were supported, obtaining bsmim@S and bsHim@S. Both materials were characterized and tested as heterogeneous catalysts in the transesterification of p-nitrophenyl acetate with methanol and in the esterification of acetic acid with isoamyl alcohol. In both studied reactions the developed supported materials (TSILs@S) were capable to achieve product yields similar to those of homogeneous systems. Differently to the unsupported homogeneous TSIL, which only in a few cases can be separated by transfer of the product to a different phase, separation and recovery of TSILs@S can be easily performed. These advantages allow the design of ecological solvent-free processes that use recyclable heterogeneous catalysts and low temperatures.